2016
DOI: 10.1158/0008-5472.can-15-1208
|View full text |Cite
|
Sign up to set email alerts
|

Immunotargeting of Antigen xCT Attenuates Stem-like Cell Behavior and Metastatic Progression in Breast Cancer

Abstract: Resistance to therapy and lack of curative treatments for metastatic breast cancer suggest that current therapies may be missing the subpopulation of chemoresistant and radioresistant cancer stem cells (CSC). The ultimate success of any treatment may well rest on CSC eradication, but specific anti-CSC therapies are still limited. A comparison of the transcriptional profiles of murine Her2 þ breast tumor TUBO cells and their derived CSC-enriched tumorspheres has identified xCT, the functional subunit of the cys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 49 publications
(57 reference statements)
5
142
0
Order By: Relevance
“…1A and B, respectively), as has already been observed in previous reports. 22,24 Moreover, tumorspheres showed increased in vitro self-renewal, with respect to TUBO cells in our own experiments. This is demonstrated by the higher number of cell clones generated by tumorspheres in a limiting dilution assay (Fig.…”
Section: Tumorspheres Derived From the Murine Erbb2supporting
confidence: 62%
See 1 more Smart Citation
“…1A and B, respectively), as has already been observed in previous reports. 22,24 Moreover, tumorspheres showed increased in vitro self-renewal, with respect to TUBO cells in our own experiments. This is demonstrated by the higher number of cell clones generated by tumorspheres in a limiting dilution assay (Fig.…”
Section: Tumorspheres Derived From the Murine Erbb2supporting
confidence: 62%
“…They were propagated in vitro up to the third passage (P3, hereafter referred as tumorspheres), as previously described. 24 In vivo treatments BALB/c and C57/BL6 mice were bought from Charles River Laboratories, maintained at the Molecular Biotechnology Twenty-one days after cell injection, blood was collected and mice were sacrificed in order to analyze lung metastasis formation and immune infiltrate both by FACS and histological analysis. Lungs were removed, fixed in 4% formaldehyde solution, cut into small pieces, paraffin-embedded, sectioned and haematoxylin and eosin (H&E) stained.…”
Section: Erbb2mentioning
confidence: 99%
“…We therefore evaluated whether Cr-1 vaccination elicits a protective immune response against Cr-1 expressing CSCs. The murine mammary carcinoma cell line TUBO acquires CSC phenotypic markers when passaged three times as spheres (P3 TUBO cells) (23,34). Over three passages in spheroid culture of TUBO, we observed a gradual increase in expression of Cr-1 (Fig.…”
Section: Reduced Lung Metastasis After Vaccination In the Balb-neut Mmentioning
confidence: 86%
“…We have found that spheroid cultures of murine breast cancer cells, which are considered to be enriched in CSCs (23,34) In patients, high Cripto-1 expression in the tumor has been associated with decreased survival and could be correlated to advanced disease (12). In addition, Cr-1 has been found in the serum of breast cancer patients, suggesting its potential function as a biomarker (43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation